Foreign Direct Investment in Bangladesh: Problems and Prospects - Kafi, Md. Abdullahel; Mainuddain, Mohammad; Islam, M. Muzahidul (Journal of Nepalese Business Studies, 2008)
The issue of Foreign Direct Investment (FDI) has been receiving phenomenal attention from many governments. Bangladesh is not lagging behind from it. Economic development for the developing countries like Bangladesh is largely dependent on FDI. The major challenges for the host country are to ensure an eye-catching and conducive investment climate to foreign investors for FDI inflow. In recent years, Bangladesh has been devoting efforts for attracting FDI offering a lot of lucrative incentives and benefits. Though attempts taken to increase FDI inflow, the result achieved is not appreciable enough for Bangladesh. This paper will portray the FDI inflow since 1995 and finds out causes and reasons of low-inflow based on secondary data. It also finds out the impediments and highlighted prospects for FDI in Bangladesh and provides some recommendations for its enhancements. The Journal of Nepalese Business Studies Vol. IV, No. 1 (2007) pp. 47-61